Improving Report Generation and Delivery System of Microbiological Investigations at MRI – Sri Lanka with Concern to Turn-Around-Time, An Intervention Study - Adikari, Pamila; de Alwis, Sunil; Karunanayake, Lilani (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Background: Clinical Bacteriology Laboratory (CBL) of the Medical Research Institute (MRI) is a National Reference Laboratory in Sri Lanka. The service improvement research project aimed at improving the report generation and delivery system. Methods: The mixed-method applied to study the process. Gap identification and designing of the intervention used a qualitative approach. Quantitative methods measured the effectiveness of the improvements. A package of interventions based on total quality management (TQM) principles designed with all stakeholder participation. Results: Delay in sample transport resulted from poor communication, lack of established mechanism and weak coordination between the transport unit and wards. The paper-based report generation process was disorganized, unreliable and error-prone. Additionally, the report delivery to Hospitals revolved on the incoming ambulance or government postal service a tied-up, poorly coordinated system. The interventions promoted coordinated communication. WHONET, a free windows based Laboratory Information System and database software, developed by the World Health Organization for microbiology laboratories installed to generate reliable and accurate automated reports. Reports in PDF format delivered to end-users by secured email. Timeliness, accuracy, quality and uniformity of reports improved. Improvement in post-intervention turn-around-time was statistically significant (p<0.05). Conclusion: The interventions based on TQM principles improved the process of report generation and delivery. Laboratory automation is a feasible and effective solution in the local setting. The end-user satisfaction perceived to be high on the improvements.